2012
DOI: 10.1128/aem.07702-11
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Chicory (Cichorium intybus L.) in Pigs' Diets Affects the Intestinal Microenvironment and the Gut Microbiota

Abstract: The content and composition of prebiotic plant fiber in the diet is important in promoting gut-related health. This study investigated the effects of the dietary inclusion of chicory forage and roots on the intestinal microenvironment of pigs. Thirty-sevenweek-old pigs were fed 1 of 5 diets for 18 days, including a cereal-based control diet and 4 diets with the inclusion of 80 and 160 g kg ؊1 of body weight chicory forage (CF80 and CF160), 80 g kg ؊1 chicory root (CR80), and a mix of 80 g kg ؊1 forage and 80 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 32 publications
9
83
3
Order By: Relevance
“…Moreover, positive correlations were observed between the intake of dietary fiber, NSP, and cellulose and the abundance of butyrate-producing bacteria, whereas the same fiber fractions decreased the concentration of acetic and propionic acid. Liu et al (2012) found a positive correlation between butyrate-producing bacteria and acetic acid in colon. It is well known that metabolic cross-feeding commonly occurs within the gut, and that butyrate-producing bacteria are able to utilize acetate (Barcenilla et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, positive correlations were observed between the intake of dietary fiber, NSP, and cellulose and the abundance of butyrate-producing bacteria, whereas the same fiber fractions decreased the concentration of acetic and propionic acid. Liu et al (2012) found a positive correlation between butyrate-producing bacteria and acetic acid in colon. It is well known that metabolic cross-feeding commonly occurs within the gut, and that butyrate-producing bacteria are able to utilize acetate (Barcenilla et al, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…However, it is clear that the small intestine in pigs harbors a significant microbial population (Leser et al, 2002). It has also been shown that the microbial community composition cluster in accordance with gut segment, with higher diversity in colon and fecal samples compared with ileal digesta samples Liu et al, 2012). Indeed, the fermentation of NSP is suggested to be a result of a combined action of several bacteria (Van Laere et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by some authors (18,24,28) indicates that adding fructans to feed mixtures for pigs increases production of short-chain organic acids in the digestive tract. In the present study, the highest total content of selected SCFAs in the cecum was noted in groups IV (82.4 µM/g) and III (79.8 µM/g), which received inulin in their feed (group III) or inulin with a probiotic (group IV), with the highest concentrations noted for propionic and butyric acid, and the lowest for isobutyric acid.…”
Section: Resultsmentioning
confidence: 99%